2019
DOI: 10.1016/j.jimonfin.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The implications of central bank transparency for uncertainty and disagreement

Abstract: We are thankful for receiving the Research Donation from the Bank of England to be able to purchase the Consensus Forecast Data. Highlights Explore the effects of increased transparency, inflation targeting and forward guidance on aggregate uncertainty, common uncertainty and disagreement. Provide evidence that increased transparency reduces mainly common uncertainty. Looking at disagreement only understates benefits of transparency. AbstractUsing survey data from 25 economies we provide evidence that great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
12
0
3
Order By: Relevance
“…According to Dale, Orphanides, and Osterholm (2011), Odyssean forms of forward guidance will generally provide clear and unambiguous advice. Of more direct relevance to the hypotheses examined in this paper, Kool and Thornton (2015) and Jitmaneeroj et al (2019) showed that forward guidance was associated with reduced dispersion of forecasts of interest rates. To control for the potential role of unconventional monetary policy, we use dummy variables to measure asset purchase decision (D APF it ) and forward guidance ( D FWD it ).…”
Section: The Effect Of Monetary Policy Transparency and Central Bank ...mentioning
confidence: 76%
See 2 more Smart Citations
“…According to Dale, Orphanides, and Osterholm (2011), Odyssean forms of forward guidance will generally provide clear and unambiguous advice. Of more direct relevance to the hypotheses examined in this paper, Kool and Thornton (2015) and Jitmaneeroj et al (2019) showed that forward guidance was associated with reduced dispersion of forecasts of interest rates. To control for the potential role of unconventional monetary policy, we use dummy variables to measure asset purchase decision (D APF it ) and forward guidance ( D FWD it ).…”
Section: The Effect Of Monetary Policy Transparency and Central Bank ...mentioning
confidence: 76%
“…Third, since the Great Recession the BOE has undertaken unprecedented forms of monetary policy such as asset purchase facility and forward guidance. Recent studies show that unconventional monetary policy actions have been associated with the reduction in disagreement about interest rate forecasts (Jitmaneeroj et al, 2019;Kool & Thornton, 2015). Finally, as the central bank aims to manage the private sector's expectations, the effectiveness of monetary policy depends on the credibility economic agents have in central bank's ability to achieve its objectives (e.g., Blinder, 2000;Cecchetti & Krause, 2002;de Haan et al, 2005;Dovern et al, 2012;Henckel, Menzies, Moffatt, & Zizzo, 2019).…”
Section: The Effect Of Monetary Policy Transparency and Central Bank ...mentioning
confidence: 99%
See 1 more Smart Citation
“…В связи с этим функционирование банковской системы и ее звеньев должно быть четким, слаженным, действенным, динамичным и нацелено обеспечить успешное развитие всей экономики страны. Иными словами, «чем больше прозрачности в отношении проводимой денежно-кредитной политики страны, тем меньше разногласий будет между элементами банковской системы» [15].…”
Section: совершенствование административно-правового регулирования баunclassified
“…For example, Adrian and Khan (2019) characterize transparency as a vital component that is bridging independence and accountability and allows independent central banks to prove their effectiveness and public accountability. Finally, the literature documents that central bank transparency reduces uncertainty of interest rates and inflation (Jitmaneeroj et al, 2019), lowers stock price volatility (Papadamou et al, 2014), enhances monetary policy effectiveness (Papadamou et al, 2015), reduces the idiosyncratic risk of banking institutions (Andries et al, 2020), and contributes to financial stability (De Mendonca and De Moraes, 2018).…”
Section: Introductionmentioning
confidence: 99%